HIPERTENSI DAN TERAPI SENAM PADA LANSIA DI PUSKESMAS SUNGAI PANAS - Trisya Yona Febrina; Didi Yunaspi, Made Tantra Wirakesuma, Mawardi Badar (Adiba Aisha Amira, 2024)
Hypertension/High blood pressure is a condition where blood pressure is higher than normal, or is often called high blood pressure. Hypertension is an increase in systolic blood pressure of more than 140 mmHg or more and diastolic of more than 90 mmHg or more. This has an impact on the blood vessels of older people who are susceptible to hypertension. One way to overcome this problem is to do exercise as a non-pharmacological therapy. Tera gymnastics is a combination of breathing exercises and body movements. This counseling aims to determine the impact of therapeutic exercise on reducing blood pressure in elderly people suffering from hypertension at the Sungai Panas Health Center. Activities show that 80% of elderly people's knowledge about hypertension is good, 65% of elderly people have a positive attitude towards hypertension. This shows that the elderly have good knowledge and a positive attitude.